If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 2t + -6 = 9t + 20 + -5t Reorder the terms: 8 + -6 + 2t = 9t + 20 + -5t Combine like terms: 8 + -6 = 2 2 + 2t = 9t + 20 + -5t Reorder the terms: 2 + 2t = 20 + 9t + -5t Combine like terms: 9t + -5t = 4t 2 + 2t = 20 + 4t Solving 2 + 2t = 20 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 2 + 2t + -4t = 20 + 4t + -4t Combine like terms: 2t + -4t = -2t 2 + -2t = 20 + 4t + -4t Combine like terms: 4t + -4t = 0 2 + -2t = 20 + 0 2 + -2t = 20 Add '-2' to each side of the equation. 2 + -2 + -2t = 20 + -2 Combine like terms: 2 + -2 = 0 0 + -2t = 20 + -2 -2t = 20 + -2 Combine like terms: 20 + -2 = 18 -2t = 18 Divide each side by '-2'. t = -9 Simplifying t = -9
| 6x^5-10x^4/2x^2 | | 9x-7x=-36 | | 78x-7= | | p+38=22 | | ln(x)+8=22 | | 17+5=x+3 | | x+x+27+4x-33=816 | | 2/9x10/12x18/25 | | 3.66=5.5x+3 | | 95=y/4-18 | | 3.33=5.5x+3 | | 21x^2+11x-2=0 | | 9x-5=4(3x-2) | | x^5*x= | | 7a+2=2a+4 | | 78/54 | | 400=70t-3t^2 | | 7-27/8 | | -4(-2x-7)6x-7= | | 2(3-m)-3m(m-3)=(6-2m)-3m | | -5x^3= | | 2(5xy-6)+4(8+3x)-6=0 | | 4x/9-8y=5 | | 297=(x+2)3x | | 20+4b-5a-ab= | | 2x+3y=49 | | (11x/4)=(2x/5) | | -6+2(5+8)-3= | | -3x+4x-2+5= | | (8x-3)(x+4)= | | 2x-5/8y=1/6 | | 6p+29-34=919 |